Hepatitis B core-related antigen serum levels may be a predictor of acute flare of chronic hepatitis B among pregnant women in the immune-tolerant phase of chronic HBV infection after short-course antiviral therapy. Issue 1 (31st December 2023) - Liu, Ruyu; Yang, Liu; Jiang, Tingting; Lu, Yao; Zhang, Lu; Shen, Ge; Wu, Shuling; Chang, Min; Hao, Hongxiao; Hu, Leiping; Gao, Yuanjiao; Xu, Mengjiao; et al.
ABSTRACT: Background: Studies have shown acute flares of chronic hepatitis B (CHB) might be related to immunologic changes that occur during pregnancy. However, the indicators for predicting acute flares of CHB among pregnant women still need further study. We aimed to distinguish the relevance between serum levels of HBcrAg and acute flares of CHB in pregnant women in the immune-tolerant phase of chronic HBV infection after short-course antiviral therapy. Methods: A total of 172 chronic HBV-infected pregnant women who were judged to be in the immune-tolerant phase were recruited in our research. All patients received short-course antiviral therapy with TDF. The biochemical, serological, and virological parameters were measured using standard laboratory procedures. The serum levels of HBcrAg were tested by ELISA. Results: Fifty-two (30.2%) out of 172 patients had acute flares of CHB. At postpartum week 12 (TDF cessation), serum HBcrAg (OR, 4.52; 95% CI, 2.58–7.92) and HBsAg (OR, 2.52; 95% CI, 1.13–5.65) were associated with acute flares of CHB. The serum HBcrAg levels were beneficial for confirmation of patients with acute flares of CHB, with an area under the ROC curve of 0.84 (95% CI, 0.78–0.91). Conclusions: For pregnant women with chronic HBV infection in the immune-tolerant phase, serum HBcrAg and HBsAg levels at postpartum week 12 were associated with acute flares of CHB after short-course antiviral therapy with TDF. The serum HBcrAg level can correctly identify acute flares of CHB and may be a predictor of the need for continuing antiviral therapy after 12 weeks postpartum.